1976
DOI: 10.1002/1097-0142(197604)37:4<1944::aid-cncr2820370446>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Craniopharyngiomas. A clinical and pathological review

Abstract: Two hundred and forty-five cases of craniopharyngiomas were obtained from the files of the AFIP and reviewed statistically with reference to their gross and microscopic appearance and clinical data. The majority of the tumors were cystic and microscopically, cysts were formed by squamous epithelial maturation, by degeneration of the stellate cells at the centers of adamantinomatous nests, or by degeneration of the stroma. Transitional forms were seen between adamantinomatous and squamous epithelium and keratoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
122
0
2

Year Published

1987
1987
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 228 publications
(133 citation statements)
references
References 6 publications
9
122
0
2
Order By: Relevance
“…The clinicopathologic study of Duff et al (2000) also found lethargy, visual deterioration, papilledema, hydrocephalus, and adhesive tumor growth to be associated with a poorer outcome. Most studies of craniopharyngiomas indicate that radiation treatment is strongly associated with tumor regression or lack of recurrence (Duff et al, 2000;Eldevick et al, 1996;Petito et al, 1976). No radiation therapy was administered in the present case.…”
Section: Discussionmentioning
confidence: 61%
See 4 more Smart Citations
“…The clinicopathologic study of Duff et al (2000) also found lethargy, visual deterioration, papilledema, hydrocephalus, and adhesive tumor growth to be associated with a poorer outcome. Most studies of craniopharyngiomas indicate that radiation treatment is strongly associated with tumor regression or lack of recurrence (Duff et al, 2000;Eldevick et al, 1996;Petito et al, 1976). No radiation therapy was administered in the present case.…”
Section: Discussionmentioning
confidence: 61%
“…In addition to remote metastases (Gupta et al, 1999;Ito et al, 2001), rare examples of craniopharyngioma arise in ectopic locations, including the pineal gland (Solarski et al, 1978), sphenoid bone (Cooper and Ransohoff, 1972), cerebellopontine angle (Gökalp et al, 1991), optic chiasm (Duff and Levine, 1983), and nasopharynx (Majlessi et al, 1978). Neuro-Oncology A P R I L 2 0 0 2 Directly or indirectly, neuroimaging (Crotty et al, 1995;Sorva et al, 1987) and clinicopathologic studies (Crotty et al, 1995;Petito et al, 1976) have documented the occurrence of 2 forms of craniopharyngioma, the adamantinomatous and papillary variants. Adamantinomatous-type tumors predominate, are suprasellar in location, and often show intrasellar extension (Burger and Scheithauer, 1994;Duff et al, 2000;Petito et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations